Fruit Peel Eco-Enzyme Precipitate Improves Vegetative Growth and Biomass of Solanum pimpinellifolium L. - Rosana Dewi; Yuni Satitiningrum; Iqlima Amelia (BIOPENDIX, 2026)
Eco-enzyme precipitate derived from fruit peel fermentation has emerged as a promising organic input for sustainable agriculture. This study aimed to evaluate the effects of eco-enzyme precipitate on the vegetative growth of Solanum pimpinellifolium L. A completely randomized design with five treatment levels (P0–P4) was applied. Growth parameters observed included plant height, number of leaves, leaf width, fresh weight, and dry weight. Data were analyzed using one-way ANOVA followed by Tukey’s test at a 5% significance level. The results demonstrated that eco-enzyme precipitate significantly enhanced all measured parameters (p < 0.05). The highest treatment level (P4) consistently produced superior growth performance, with plant height reaching 11.70 cm, leaf number 9 leaves, leaf width 1.63 cm, fresh weight 4.85 g, and dry weight 0.93 g, compared to the control treatment (P0). The progressive increase across treatments indicates a dose-dependent response associated with improved nutrient availability, enhanced photosynthetic capacity, and greater biomass accumulation. The marked rise in dry weight confirms that growth improvement reflected genuine physiological gain rather than temporary water retention. These findings highlight the agronomic potential of eco-enzyme precipitate as a low-cost organic fertilizer capable of improving vegetative growth while simultaneously supporting waste valorization and circular agricultural systems. The study provides empirical evidence that fruit peel-derived eco-enzyme precipitate can serve as a sustainable alternative input for small-scale farming, contributing to environmentally responsible agricultural practices.